Représenter la désobéissance civile par le dessin, Cuadernos del 15M de Enrique Flores - François Malveille (Amnis)
Spanish cartoonist Enrique Flores was an actor and witness of the 15M 2011 in Madrid. He produces and broadcasts a graphic report that strikes by its quality and relevance. This alternative representation of a political movement marked by the notion of civil disobedience questions. These drawings show a state of mind, a militant disposition, a research that reflects a way of rethinking politics at the beginning of the 21st century. Enrique Flores makes his blog an alternative media and the freedom of drawing joins the political freedom of the demonstrators. This alternative representation reflects a moment and is associated with a movement. His drawings show the movement, the people, the slogans and constitute a demonstration always visible on his blog 4 Ojos in 2023.